1979
DOI: 10.3758/bf03209652
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory in rats: Resistance to retroactive interference

Abstract: Treatments that interfere with animals' short-term retention (e.g., in delayed matching-tosample] were studied using a spatial memory task. Rats performed in an eight-arm radial maze in which choosing each arm without repetition was the optimal behavior. Performances were interrupted between fourth and fifth choices for a delay of 15 sec to 2 min. A variety of events occurring during the delay interval did not disrupt memories for prior choices (as assessed by the accuracy of postdelay choices). The ineffectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
65
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(71 citation statements)
references
References 11 publications
5
65
1
Order By: Relevance
“…Very high choice accuracy has been obtained in mazes with up to 17 arms (Olton, Collison, & Werz, 1977) or even 24 arms in a hierarchical maze (Roberts, 1979). Furthermore, rats maintain their performance in spite of prolonged interruption in the middle of a test (Beatty & Shavalia, 1980), following sensory perturbation during an interruption (Maki, Brokofsky, & Berg, 1979), or even after trials in other radial mazes during the interruption (Cook & Brown, 1985). Kraemer, Gilbert, and Innis (1983) have shown that rats rely preferentially on extramaze cues but are also capable of highly accurate choices when trained with intramaze cues, even when the intramaze configuration is altered on each trial.…”
mentioning
confidence: 99%
“…Very high choice accuracy has been obtained in mazes with up to 17 arms (Olton, Collison, & Werz, 1977) or even 24 arms in a hierarchical maze (Roberts, 1979). Furthermore, rats maintain their performance in spite of prolonged interruption in the middle of a test (Beatty & Shavalia, 1980), following sensory perturbation during an interruption (Maki, Brokofsky, & Berg, 1979), or even after trials in other radial mazes during the interruption (Cook & Brown, 1985). Kraemer, Gilbert, and Innis (1983) have shown that rats rely preferentially on extramaze cues but are also capable of highly accurate choices when trained with intramaze cues, even when the intramaze configuration is altered on each trial.…”
mentioning
confidence: 99%
“…Rodriguez et al, 1993), has revealed that spatial memory in rats appears resistant to disruption when the interpolated ('between-tests') event is different to the original learned task (e.g. Maki et al, 1979). However, if there is a large amount of interpolated experience, or if the interpolated event is very similar to the original task, it does appear that interference can occur (Roberts, 1981).…”
mentioning
confidence: 99%
“…Moreover, intramaze cues, like possible odor trails, contribute little if anything to control of choices (Maki, Beatty, Hoffman, et al, 1984;Olton & Samuelson, 1976). The rat's amazing performance in the longdelay version of the radial maze task thus appears to involve a robust form of spatial working memory (Maki, 1985a;Maki, Beatty, Hoffman, et aI., 1984), which may persist over such lengthy delays because of its resistance to retroactive interference from many kinds of delayinterval stimuli (Beatty & Shavalia, 1980a;Maki, Brokofsky, & Berg, 1979;Shavalia, Dodge, & Beatty, 1981).…”
mentioning
confidence: 99%